Low-Carbon Economic Dispatch for Integrated Energy System Through the Dynamic Reward and Penalty Carbon Emission Pricing Mechanism - Wu, Yingjun; Shi, Zhanyu; Lin, Zhiwei; Zhao, Xiang; Xue, Tao; Shao, Junjie (Frontiers in Energy Research, 2022)
The integrated energy system (IES) plays a key role in energy conservation and emission reduction. In order to realize the low-carbon economic dispatch of the IES, current studies usually utilize the fixed and the ladder-type pricing mechanism-based carbon emission unit cost (CEUC) in the optimal dispatch model. However, those mechanisms fail to take carbon emissions levels of the system into account, and the relevant parameters, such as the interval length, are hard to set. In order to tackle this challenge, a CEUC model with a dynamic reward and penalty pricing mechanism (DRPPM) is constructed. And then an optimal dispatch model to minimize the comprehensive operation cost, including the carbon emission cost, the energy purchasing cost, and the equipment operation cost, is proposed. At last, an actual electricity–heat–cooling–gas IES is employed to analyze the impact of parameters of the CEUC model on the dispatch.